2019
DOI: 10.1002/cam4.1889
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐infiltrating CD8+ T‐cell density is an independent prognostic marker for oral squamous cell carcinoma

Abstract: BackgroundThe presence of tumor‐infiltrating lymphocytes (TILs) is associated with improved survival in head and neck squamous cell carcinoma. However, the prognostic value of TILs remains unclear in oral squamous cell carcinoma (OSCC).MethodsWe evaluated the associations between tumor‐infiltrating CD8+ T‐cell density and survival in five distinct compartments in 139 OSCC cases.ResultsThere was a significant association between increased tumor‐infiltrating CD8+ T cells and their distribution. High parenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
96
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 42 publications
12
96
2
2
Order By: Relevance
“…However, the objective response rates to checkpoint blockade immunotherapy only range from 16 to 25% [11,12]. As recent studies indicated, immunerelated biomarkers could define not only the patients' immune state, but also the biological behavior of HNSCC [13][14][15]. For example, tumor-infiltrating lymphocytes (TILs) in the tumor microenvironment could contribute to improved prognosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the objective response rates to checkpoint blockade immunotherapy only range from 16 to 25% [11,12]. As recent studies indicated, immunerelated biomarkers could define not only the patients' immune state, but also the biological behavior of HNSCC [13][14][15]. For example, tumor-infiltrating lymphocytes (TILs) in the tumor microenvironment could contribute to improved prognosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Because HLA class I expression at the IF was associated with decreased cancer cell proliferation and metastasis based on survival, it might exert a protective effect against cancer. In addition, we previously reported that CD8⁺ T cell density at the IF was an indicator of tumor recurrence and prognosis 19 . The cases analyzed in our previous and present studies largely overlapped, but in the present study, we analyzed the relationship between CD8⁺ T cell density and HLA class I expression.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, tissue sections were incubated with a primary mAb against pan‐cytokeratin (1:200, clone AE1/AE3; Abcam) to detect multiple cytokeratins and identify tumor cells. CD8 + T cells were stained according to our previous report 19 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…STAD is a highly heterogeneous cancer, and tumor heterogeneity is instrumental in immune evasion [24][25][26][27][28] . In fact, several studies have shown that tumor infiltrating immune cells are prognostic markers for cancer progression [29][30][31] . Therefore, we hypothesized that VGLL3 expression is associated with immune infiltration in STAD tumors, and a potential marker of the tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%